Vibrio alginolyticus Reprograms CIK Cell Metabolism via T3SS Effector VopS to Promote Host Cell Ferroptosis - Weijie Zhang; Chao Huang; Zhihang Chen; Dawei Song; Yujia Zhang; Shuai Yang; Na Wang; Jichang Jian; Huanying Pang (Animals)
Vibrio alginolyticus is a Gram-negative pathogen of both marine animals and humans, resulting in significant losses for the aquaculture industry. Emerging evidence indicates that V. alginolyticus manipulates cell death for its pathogenicity, but the underlying molecular mechanisms remain unclear. Here, a gene designated vopS in V. alginolyticus HY9901 was identified, which was predicted to encode the T3SS effector protein. To determine whether VopS contributes to the pathogenesis of V. alginolyticus, the ΔvopS mutant strain was constructed and phenotypically characterized. The deletion of VopS not only reduced the ability to secrete extracellular proteases and virulence but also affected the expression of the T3SS genes. Furthermore, VopS was cytotoxic and induced apoptosis, as confirmed by elevated LDH and the activation of caspase-3. Metabolomic analysis revealed considerable metabolomic disruptions upon V. alginolyticus infection. The VopS effector induced host cell ferroptosis by promoting the synthesis of adrenic acid, depleting cellular glutathione, and subsequently increasing the accumulation of ferrous (Fe2+). Taken together, our findings provide that the VopS effector is an essential virulence factor of V. alginolyticus, which can lead to ferroptosis.